THE ISSUE OF WOMEN'S TRAGIC DESTINY IN THE WORKS OF ALISHER NAVAIY AND THOMAS HARDY (Universal International Scientific Journal, 2026)
This article analyzes the issue of the tragic fate of the image of a woman in the works of Alisher Navoi from an artistic, aesthetic and socio-philosophical perspective. In the poet's work, the image of a woman is not limited to the image of love and beauty, but is depicted against the background of complex social relations, social pressure and moral contradictions. During the study, the main causes of the tragedy of a woman in Navoi's epics are indicated as the patriarchal social environment, the restriction of women's choice and the denial of spiritual values ​​by society. The article argues that the tragedy is not the woman's personal fault, but the consequence of social injustice. The results of the study show that Navoi's aesthetic views are an important theoretical source in studying the problems of the fate of a woman in modern literature.
Keywords: Alisher Navoi, image of a woman, tragic fate, social environment, love, spiritual purity.